When the Walls Come Down: Indonesian-Sino-Vietnamese Normalization and the End of the Asian Cold War - Dan McCoy (Muslim Politics Review, 2026)
How did the Cold War conclude in the Asia Pacific? The European Cold War ended via a groundswell of social, political, and cultural movements concurrent with high-level U.S.-Soviet summits during the 1980s and early 1990s. By comparison, Asia terminated its Cold War in a more muted fashion. The Asian Cold War ended primarily through monumental maneuvers in the international political arena by surmounting ideological schisms, security dilemmas, and incongruous economic systems. Sino-Indonesian normalization came to fruition in August 1990, ending a 23 year-long freeze in relations. China and Vietnam fully restored bilateral relations in November 1991. The restoration of relations between Indonesia, Vietnam, and China pivoted the Asia Pacific away from Cold War-era confrontation toward progressively cooperative multilateralism at the dawn of the post-Cold War. Shifting structural mechanisms and power politics reshaped Indonesian-Sino-Vietnamese relations as the triumvirate addressed long-standing hostilities to reach meaningful economic, political, and security cooperation to anticipate the post-Cold War international order. The trio’s myriad diplomatic interactions during the late 1980s and early 1990s fused national interests with a mutual aspiration toward heightened regional autonomy, as regional actors asserted themselves more boldly amid a rapid recomposition of the Asia Pacific chessboard. The impact of the trilateral rapprochement reverberates into the present security and political configuration of the region.